Early Memories as a Guide to Client Movement Through Life - Slavik, Steve (Canadian Journal of Counselling and Psychotherapy, 2011)
Early memories are a projective tool which Adlerian psychologists have been using since the 1930's. Their elicitation and interpretation allows a counsellor to make accurate guesses about an individual's typical way of coping with life. This paper outlines the theory of the significance of early memories and a procedure for their elicitation and interpretation. It provides several examples of their use in an encouraging therapeutic context.